2017
DOI: 10.19175/recom.v7i0.1135
|View full text |Cite
|
Sign up to set email alerts
|

O absente�smo entre os trabalhadores de sa�de de um hospital p�blico do sul do Brasil

Abstract: RESUMOObjetivo: caracterizar o perfil de adoecimento dos trabalhadores de saúde e seu absenteísmo, em um hospital público na região sul do Brasil. Método: descritivo, quantitativo e retrospectivo, no qual foi avaliado o absenteísmo referente ao ano de 2013, captado pela ferramenta "Sistema de Monitoramento da Saúde do Trabalhador de Enfermagem". Resultados: o perfil dos trabalhadores afastados em sua maioria era do sexo do trabalho, totalizando 4.619 dias perdidos. Observou-se a prevalência de doenças do siste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
20

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 10 publications
1
12
0
20
Order By: Relevance
“…Nurses usually experience a double working day, associating the housework, caring for family and children, in addition to their actual working day, causing an overload of tasks to be performed. On the other hand, one of the justifications for the multiple employment relationship is low wages, and with the weakness of the contracts in addition to low wages/ salaries, there is no guarantee of social security (26)(27) .…”
Section: Discussionmentioning
confidence: 99%
“…Nurses usually experience a double working day, associating the housework, caring for family and children, in addition to their actual working day, causing an overload of tasks to be performed. On the other hand, one of the justifications for the multiple employment relationship is low wages, and with the weakness of the contracts in addition to low wages/ salaries, there is no guarantee of social security (26)(27) .…”
Section: Discussionmentioning
confidence: 99%
“…One study (Santa-Marinha et al, 2018) referred to in its findings to chronic non-communicable diseases as the main causes of absenteeism, especially depressive disorders. Research results also (Brey et al, 2017;Daniel, Koerich, & Lang, 2017;Galindo et al, 2017) indicate as main causes of disease absenteeism disorders of the musculoskeletal system, followed by mental disorders. Still in this regard, research carried out in Vietnam (Luan et al, 2018) found that nurses with anxiety who were absent from work had a higher prevalence of musculoskeletal diseases than those who did not present these factors.…”
Section: Discussionmentioning
confidence: 90%
“…O absenteísmo em trabalhadores de um hospital público do Sul do Brasil também foi frequente e os problemas respiratórios também apareceram como uma das principais causas deste tipo de afastamento, identificando 152 trabalhadores que haviam sido afastados do trabalho devido afecções do sistema respiratório, corroborando com a presente pesquisa 22 .…”
Section: Discussionunclassified